Pengujian Slim-tube untuk Memperkirakan Minimum Miscible Pressure pada Studi CO 2 Enhanced Oil Recovery - IGS Budiaman (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Implementation of enhanced oil recovery (EOR) usingcarbon dioxide (CO2) to increase oil recovery has been widely implemented in the world, but in Indonesia, especially in Pertamina is still in the feasibility study stage. One of the parameters is very important in supporting the successful implementation of CO2 EOR is the thermodynamic properties in the form of minimum miscible pressure (MMP). Considering Indonesia is a tropical country and the oil reservoir is relatively deep, so that the temperature of the reservoir is relatively high which would provide great value of MMP and will have an impact on the oil recovery factor ability.MMP testing is very important to be done in the laboratory using the slim-tube. On the condition of CO2 MMP initially is being mixed with short to medium-chain hydrocarbons in the reservoir, then further with heavier hydrocarbons. Mixing CO2 into oil will lead to occurrence of oil volume swelling and decrease its viscosity. The phenomenonof swelling volume of oil in the reservoir may lead to increased capillary pressure so that the oil is easier to flow. While the decline in oil viscosity increases mobility of oil or in other words will lower the water-oil mobility ratio. Decreased mobility ratio ofthe water-oil may increase oil reserves that can be produced. Based on the slim-tube experiments in the laboratory using a sample of oil field